1992
DOI: 10.1128/jb.174.22.7090-7097.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mutants carrying conditionally lethal mutations in outer membrane genes omsA and firA (ssc) are phenotypically similar, and omsA is allelic to firA

Abstract: We have previously identified the gene (the ssc gene) defective in the thermosensitive and antibiotic-supersusceptible outer membrane permeability mutant SS-C of Salmonella typhimurium and shown that this gene is analogous to the Escherichia coli gene firA (L. Hirvas, P. Koski, and M. Vaara, EMBO J. 10:1017-1023, 1991). Others have tentatively implicated firA in a different function, mRNA synthesis. Here we report that the defect in the thermosensitive outer membrane omsA mutant of E. coli (T. Tsuruoka, M. Ito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…A more sensitive, high-resolution probe for nascent PG insertion in nonfixed cells was recently developed by Daniel and Errington (22). These authors used a fluorescent derivative of the antibiotic vancomycin (a cell wall synthesis inhibitor that binds specifically to PG intermediates) to label nascent PG in gram-positive bacteria by fluorescence microscopy (note that gram-negative bacteria do not stain because their outer membrane presents a permeability barrier to vancomycin) (169). This novel staining method revealed that, at least in B. subtilis, synthesis of the wall occurs in a helical pattern over the cylindrical part of the cell and also specifically at the septum in dividing cells (Fig.…”
Section: Mreb Filaments Govern Cell Morphogenesis By Actively Directimentioning
confidence: 99%
“…A more sensitive, high-resolution probe for nascent PG insertion in nonfixed cells was recently developed by Daniel and Errington (22). These authors used a fluorescent derivative of the antibiotic vancomycin (a cell wall synthesis inhibitor that binds specifically to PG intermediates) to label nascent PG in gram-positive bacteria by fluorescence microscopy (note that gram-negative bacteria do not stain because their outer membrane presents a permeability barrier to vancomycin) (169). This novel staining method revealed that, at least in B. subtilis, synthesis of the wall occurs in a helical pattern over the cylindrical part of the cell and also specifically at the septum in dividing cells (Fig.…”
Section: Mreb Filaments Govern Cell Morphogenesis By Actively Directimentioning
confidence: 99%
“…coli and S . typhimurium strains harbouring mutations in the lipid A biosynthesis genes lpxA and lpxD (Galloway & Raetz, 1990;Hirvas et al, 1991a;Helander et al, 1992Helander et al, , 1993Vuorio & Vaara, 1992b). However, the antibiotic sensitivity of LH530 was not reverted by ZpxA and ZpxD indicating that it did not harbour mutations in these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the ratio of LPS to phospholipid biosynthesis. The ratio of LPS and phospholipid biosynthesis in LH530 and its derivatives was assayed (Vuorio & Vaara, 1995) after labelling their fatty acids with radioactive acetate in vivo at 28 "C, 37 "C and 42 "C. In detail, 5 x lo8 bacterial cells (from fresh LB plates grown at 28 "C) were suspended in 5 ml LB broth. After growing (with stirring) for 1 h at the selected temperature (28 "C, 37 "C or 42 "C),lO p1 (074 MBq) [14C]acetate (sodium salt, CFA229, specific activity 1.89 GBq mmol-l ; Amersham) was added and growth was continued for an additional 2 h. The cells were harvested by centrifugation (4300 r.p.m., Heraeus megafuge), washed with 2.5 ml saline, transferred with 1 ml of saline into Sarstedt tubes (1 ml) and collected by centrifugation.…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…Sequencing of firA of E. coli revealed that it is 88% identical to ssc of S. typhimunium and that the corresponding proteins are 96% identical (10). Quite recently, Vuorio and Vaara (64) reported that another antibiotic-supersusceptible mutant, the so-called omsA mutant strain CDH23-213 of E. coli (52), resembles SH7622 phenotypically and that omsA is allelic to firA. To date, omsA of CDH23-213 and ssc-1 of SH7622 are the best-characterized firA alleles known.…”
mentioning
confidence: 99%